Familial Opioid Misuse and Family Cohesion: Impact on Family Communication and Well-being. (December 2019) - Alhussain, Khalid; Shah, Drishti; Thornton, James Douglas; Kelly, Kimberly M.
Abstract : Objectives: This study aimed to understand family communication and overall well-being of young adults in the context of familial opioid misuse using the family systems framework. Methods: A cross-sectional, mixed-methods, online survey of young adults aged 18 to 30 years (n=137) was conducted. A cluster analysis was performed based on family organization and structural characteristics. MANCOVA was utilized to compare groups identified using the cluster analysis in terms of (1) family's belief about opioid misuse, (2) worry regarding opioid misuse, (3) family communication, and (4) overall well-being of young adults. Results: A cluster analysis resulted in three groups (group 1: no familial opioid misuse with high family cohesion; group 2: familial opioid misuse with moderate family cohesion; group 3: those with/without familial opioid misuse and low family cohesion). Group 3 had the lowest family communication compared to group 1 and group 2 ( P <0.001 and P =0.001, respectively) and had lower overall well-being compared to group 1 ( P =0.008). Group 2 had a higher worry score than group 1 ( P <0.001). Qualitative analysis using Labov's narrative analysis elucidated that having someone misusing opioids with other substances (eg, alcohol) in the family can negatively impact the emotions of family members. Conclusions: Our findings indicated that family cohesion had a greater impact on family communication and overall well-being of young adults even in the presence of familial opioid misuse. This suggests that higher family cohesion may positively influence young adults to cope with issues related to familial opioid misuse.